Safety evaluation of human peripheral blood mononuclear cells in naive rats:a chronic toxicitystudy - Supartono, Basuki; Farida, Siti; Suhandono, Sony; Yusuf, Ahmad Aulia (Bangladesh Journal of Medical Science, 2022)
Human peripheral blood mononuclear cells (PBMC) are widely used within tissue engineering therapy, thus, the evaluation of their safety is mandatory. The present study aims to assess the safety of human PBMC transplantations in naive rats in terms of chronic toxicity. Rats received intravenous injections of human PBMC with doses of 105, 106, or 107 cells (n = 5/group/sex) every month for three months without administration of any immunosuppressant drugs. We evaluated clinical, physical, laboratory, and pathology parameters. No morbidity, mortality, or significant differences occurred within all of the tested parameters between control and experimental groups until the finalization of the study. In conclusion, the current work indicates that human PBMC transplantation in naive rats did not induce chronic toxicity reaction. Bangladesh Journal of Medical Science Vol. 21 No. 02 April’22 Page : 373-383